2021
DOI: 10.3758/s13428-021-01638-x
|View full text |Cite
|
Sign up to set email alerts
|

GFMT2: A psychometric measure of face matching ability

Abstract: We present an expanded version of a widely used measure of unfamiliar face matching ability, the Glasgow Face Matching Test (GFMT). The GFMT2 is created using the same source database as the original test but makes five key improvements. First, the test items include variation in head angle, pose, expression and subject-to-camera distance, making the new test more difficult and more representative of challenges in everyday face identification tasks. Second, short and long versions of the test each contain two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Participants completed 80 face comparison trials (40 match and 40 nonmatch) from the Glasgow Face Matching Task 2-Short Form (GFMT2-S; White et al, 2021). The GFMT2-S is an updated version of the GFMT that was created to be more difficult and representative of real-world face identification tasks (i.e., variation in head angle, pose, expression, and image quality) than the original task.…”
Section: Face Comparisonmentioning
confidence: 99%
“…Participants completed 80 face comparison trials (40 match and 40 nonmatch) from the Glasgow Face Matching Task 2-Short Form (GFMT2-S; White et al, 2021). The GFMT2-S is an updated version of the GFMT that was created to be more difficult and representative of real-world face identification tasks (i.e., variation in head angle, pose, expression, and image quality) than the original task.…”
Section: Face Comparisonmentioning
confidence: 99%
“…Also, why are they reporting problems in daily life but not on our objective tests? Could another measure beyond the CFMT, FFT and CFPT be more accurate in capturing their daily difficulties with faces, e.g., Prosopagnosia Index (Shah et al, 2015 ), the Oxford Face Matching Task (Stantic et al, 2022 ), Glasgow Face Matching Test (Burton et al, 2010 ; White et al, 2022 ), Benton Test (Murray et al, 2021 ; Rossion & Michel, 2018 ; Wang et al, 2020 ) or UNSW Faces Test (Dunn et al, 2020 )? All these questions are unanswered because excluded cases are rarely reported upon by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Face comparison Participants completed a standardized test of face comparison as a baseline control task: the Glasgow Face-Matching Task-2 (GFMT2-SA and SB; White et al, 2021 , p. 2; see upper panel of Fig. 1 ) where participants view two faces side by side and were asked ‘are these images of the same person or two different people?’ on each trial.…”
Section: Methodsmentioning
confidence: 99%
“…We then selected the 80 trials (40 match and 40 non-match) that had the highest item-to-test correlations and then divided the trials into two equally difficult versions of the test (comprising 20 match and 20 non-match trials each). We used this method as it identifies trials that are most predictive of overall test performance and provides an overall estimate of a trial’s contribution to test reliability (Guilford, 1954 ; see also White et al, 2021 and Wilmer et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation